Forage integration on farming systems in the district of Bayongbong, Garut - ., Sajimin; Prawiradiputra, Bambang R; Panjaitan, M (Indonesian Animal Sciences Society, 1999)
A study on forage integration on farming system was studied at Bayongbong of Garut District, West Java from April 1996 to April 1997. The objective of this study was to increase the availability of food and forage which are cultivated on the same land using alley cropping system. Elephant grass (Pennisetum purpureum) and gliricidia (Gliricidia sepium) Were planted on thesame area using randomized block design (RBD) with 5 treatments and 3 replications. Elephant grass and gliricidia were planted as live fence. The experimental plot which were cultivated with food crops, giving the following treatment: A. Elephant grass were planted in row with spacing of 0.5 m. B. Both elephant grass and gliricidia were planted in row with spacing of 0.5 In. C.Â Gliricidia alone were planted in row with spacing of 0.5 m. D. Experimental plot were planted with elephant grass without any life fencing. E. Experimental plot were planted with food crops as a control. Based on planting pattern com were planted on the experimental plot followed by cabbage. Cutting interval for elephant grass was 42 days while gliricidia was 60 days. Fresh and dry weight of elephant grass, gliricidia, corn and cabbage production were recorded. The results showed that there was no significant different on corn and cabbage production between treatment, while elephant grass production was significantly different (P < 0.05) among the treatments. The highest additional production of corn (1.8 kg/m2), and cabbage waste (2.5 kg/2m ) were found in the treatment. The highest elephant grass production was found in treatment A (5.1 kg/m2) followed by treatment D (4.9 kg/m2) and treatment B (4.1 kg/m2). The highest gliricidia forage production was found in the treatment B (0.6 kg/m2). It was concluded that the integration of forage and crops using alley cropping system on farm system was able to overcome the shortage of forage availability for animal production. Â Key words: Alley croping, farming system, forage